Antischistosomal activity of trioxaquines: in vivo efficacy and mechanism of action on Schistosoma mansoni. - Julien Portela; Jérôme Boissier; Benjamin Gourbal; Vincent Pradines; Vincent Collière; Frédéric Coslédan; Bernard Meunier; Anne Robert (Public Library of Science (PLoS), 2012)
Schistosomiasis is among the most neglected tropical diseases, since its mode of spreading tends to limit the contamination to people who are in contact with contaminated waters in endemic countries. Here we report the in vitro and in vivo anti-schistosomal activities of trioxaquines. These hybrid molecules are highly active on the larval forms of the worms and exhibit different modes of action, not only the alkylation of heme. The synergy observed with praziquantel on infected mice is in favor of the development of these trioxaquines as potential anti-schistosomal agents.